Exploring the antibacterial potential of plant extracts and essential oils against Bacillus thermophilus in beet sugar for enhanced sucrose retention: a comparative assessment and implications - Yousef, Mohamed M.; Zohri, Abdel-Naser A.; Darwish, Amira M. G.; Shamseldin, Abdelaal; Kabeil, Sanaa A.; Abdelkhalek, Ahmed; Binsuwaidan, Reem; Jaremko, Mariusz; Alshwyeh, Hussah Abdullah; Hafez, Elsayed E.; Saied, Essa M. (Frontiers in Microbiology, 2023)
Sugar beet is one of the tremendous sources for producing sugar around the world, however, there are a group of bacteria that grow on beet during the storage process leading to the reduction of sucrose yield. Our study focused on identifying common bacterial species that grow on beets during manufacturing and contribute to sucrose loss. The ultimate goal was to find a potential antibacterial agent from various plant extracts and oils to inhibit the growth of these harmful bacteria and reduce sucrose losses. The screening of bacterial species that grow on beet revealed that a large group of mesophilic bacteria such as Bacillus subtilis, Leuconostoc mesenteroides, Pseudomonas fluorescens, Escherichia coli, Acinetobacter baumannii, Staphylococcus xylosus, Enterobacter amnigenus and Aeromonas species, in addition to a dominant thermophilic species called Bacillus thermophiles were grown on beet during manufacturing. Application of 20 plant extracts and 13 different oils indicated that extracts of Geranium gruinum, Datura stramonium, and Mentha spicata were the best antibacterial to reduce the growth of B. thermophiles with inhibition zone equal to 40, 39, and 35 mm, respectively. While the best active oils for inhibiting the growth of B. thermophiles were from Mentha spicata and Ocimum bacilicum with an inhibitory effect of 50 and 45 mm, respectively. RAPD-PCR with different primers indicated that treating the sugar juice with the most effective oils against bacteria resulted in the appearance of new recombinant microorganisms confirming their roles as strong antibacterial products. Characterization of Mentha spicata and Ocimum bacilicum oils by GC/MS analysis identified cis-isopulegone and hexadecanoic acid, respectively, as the main two bioactive compounds with potential antibacterial activity. Analysis of five genes using DD-PCR that have been affected due to antibacterial from the highly effective oil from Mentha spicata, concluded that all were belonging to the family of protein defense. Our findings indicate that the application of these pure antibacterial plant extracts and oils would minimize the reduction of sucrose during sugar production.